Qualidade das medidas antropométricas produzidas em unidades de atenção básica à saúde da região de Botucatu-SP, Brasil - Ferreira, Milena Cristina Sendão; Detregiachi, Claudia Rucco Penteado; Oliveira, Maria Rita Marques de [UNESP] (My University, 2011)
The aim of this study was to evaluate the quality of weight measurements produced in Primary Health Care Centers in Botucatu and surroundings. 14 Health Care Centers were included, all of them located in four towns in the area of Botucatu (4,555; 5,656; 18,761 and 128,397 inhabitants). General conditions and scale calibration conditions found in those Health Care Centers were evaluated. In order to evaluate the weight accuracy obtained by the local team, 10 adult users of each Center were addressed by the rater during the service routine in order to get a new weight evaluation, immediately after the measurement made by the team. The statistic method applied for checking the weight measurement held in the Heath Care Center and the scales accuracy was the measurement error technique (MET). The results have showed that out of 19 scales, 6 of them overestimated the weight by 50 grams, 1 of them underestimated the weight by 200 grams and the others were accurate. Evaluated as a group, the result of the scale MET was 44.3g. Regarding the conformity of the measures obtained by the MET of the adults weighing in the Health Care Centers compared to the ones obtained by the researcher, the expected result was obtained in only one Center (< 100g). The results have showed data compromise, rather due to lack of health team training than due to the conditions of the equipment used for the measurement.

El objetivo del estudio fue evaluar la calidad de las medidas de peso producidas en la atención básica a la salud de la región de Botucatú (SP, Brasil). Fueron comprendidas en el estudio 14 unidades de salud, pertenecientes a cuatro municipios de la región de Botucatú (4.555, 5.656, 18.761 e 128.397 habitantes). Fueron evaluadas las condiciones generales y de calibración de las balanzas presentes en las unidades. Para evaluar la precisión del peso obtenido por el equipo local, 10 usuarios adultos de cada unidad fueron abordados por el investigador durante la rutina del servicio para una nueva evaluación comparativa de la medición, inmediatamente después de la evaluación realizada por el equipo local. El método estadístico aplicado para inquirir la conformidad de las medidas de peso y la precisión de las balanzas fue la Técnica del Error de la Medida (TEM). Los resultados mostraron que de las 19 balanzas existentes, 6 superestimaban el peso en 50 gramos, 1 lo subestimaba en 200 gramos y las otras eran precisas. Evaluadas en conjunto, el resultado de la TEM de las balanzas fue de 44,3g. En relación a la concordancia por la TEM de las medidas realizadas en las unidades con las medidas de control de los investigadores, solamente en una Unidad de Salud se obtuvo el resultado esperado (<100g). Los resultados mostraron falta de precisión de los datos producidos, más por la falta de entrenamiento del equipo de salud que por las condiciones de los instrumentos utilizados.

O objetivo do estudo foi avaliar a qualidade das medidas de peso produzidas na atenção básica à saúde da região de Botucatu-SP. A pesquisa incluiu 14 unidades de saúde, pertencentes a quatro municípios da região de Botucatu (4.555, 5.656, 18.761 e 128.397 habitantes). Foram aferidas as condições gerais e de calibração das balanças presentes nessas unidades. Para avaliação da acurácia do peso obtido pela equipe local, 10 usuários adultos de cada unidade foram abordados pela avaliadora durante a rotina do serviço para uma nova avaliação do peso, imediatamente após a aferição feita pela equipe. O método estatístico utilizado para averiguação da concordância das medidas de peso produzidas na unidade e acurácia das balanças foi a Técnica do Erro da Medida (TEM). Os resultados mostraram que das 19 balanças existentes, 6 superestimavam o peso em 50 gramas, 1 subestimava em 200 gramas e as demais apresentaram-se acuradas. Avaliadas no conjunto, o resultado da TEM da balança foi de 44,3g. Com relação à concordância das medidas pela TEM da pesagem de adultos realizadas nas unidades com àquelas da avaliadora, apenas em uma unidade obteve-se o resultado esperado (<100g). Os resultados mostraram comprometimento dos dados produzidos, mais em função da falta de treinamento da equipe de saúde, que das condições dos equipamentos utilizados para tal fi nalidade.
The quality of weight measurements produced in primary health care centers located in the region of Botucatu-SP, Brazil
Keywords: Food and nutritional surveillance; Food security; Education in service; Anthropometry; Primary health care; Vigilancia alimentaria y nutricional; Seguridad alimentaria; Educación en servicio; Antropometría; Atención primaria de salud; Vigilância alimentar e nutricional; Segurança alimentar e nutricional; Educação em serviço; Antropometria; Atenção primária à saúde